Effects of high tidal volume mechanical ventilation on production of cytokines, iNOS, and MIP-1β proteins in pigs - Vobruba, Václav; Klimenko, Oxana V; Kobr, Jiri; Cerna, Olga; Pokorna, Pavla; Mikula, Ivan; Hridel, Jan; Brantova, Olga; Martasek, Pavel (Experimental lung research, 2013)
The aim of this study was to investigate longitudinal changes of the pulmonary inflammatory process as a result of mechanical stress due to mechanical ventilation. The concentrations of IL-8, TNF-α, MIP-1β, nitrites/nitrates, and inducible nitric oxide synthases (iNOS) were investigated indicate in bronchoalveolar lavage (BAL). Twenty-three piglets were divided into three groups. Group I: animals breathing spontaneously; group II: mechanical ventilation (tidal volume (TV) = 7 mL/kg, PEEP = 5 cmH(2)O); group III: mechanical ventilation (TV = 15 mL/kg, PEEP = 0 cmH(2)0). Concentrations of BAL nitrites/nitrates from groups II and III increased during the first hour of mechanical ventilation (P = .03 and .02, respectively). The highest expression of iNOS was observed during the first hour in groups II and III. IL-8 concentration increased significantly in groups II and III. Production of TNF-α increased significantly in group III during the second and third hour (P = .01). Concentration of MIP-1β was significantly increased in groups II and III after the first hour (P = .012 and P = .008, respectively).
Keywords: Animals; bronchoalveolární lavážní tekutina; synthasa oxidu dusnatého, typ II; plicní alveoly; Nitrates; ventilace umělá s výdechovým přetlakem; umělé dýchání; Bronchoalveolar Lavage Fluid; dechový objem; Cytokines; Lung; Lung Compliance; Interleukin-8; Chemokine CCL4; Tumor Necrosis Factor-alpha; dusitany; Pulmonary Alveoli; cytokiny; prasata; chemokin CCL4; Tidal Volume; interleukin-8; TNF-alfa; Swine; Nitric Oxide Synthase Type II; Positive-Pressure Respiration; plíce; zvířata; dusičnany; Acute Lung Injury; poddajnost plic; Respiration, Artificial; akutní poškození plic; Nitrites